2009
DOI: 10.1007/s10459-009-9203-1
|View full text |Cite
|
Sign up to set email alerts
|

Are Asian international medical students just rote learners?

Abstract: A wide variety of countries are seeking to attract international medical students. This could be due to the fact that their universities not only receive the economic benefit from these students, but also because they recognise the issues of cultural diversity and pedagogical practice. This review paper draws on literature to understand more fully the learning process of Asian international students. Whereas views on learning are different across cultures, medical school teachers must understand how Asian inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 38 publications
3
36
0
Order By: Relevance
“…Moreover, Chinese students employ memorisation as an initial process in moving forward understanding rather than rote learning (Kember 2000, Tavakol andDennick 2010). Increasingly studies have found that Chinese students show little difference from their Western counterparts by being active learners and preferring meaning-based learning strategies and more interactive relationships with their teachers.…”
Section: Western Misconceptions Of Chinese Learnersmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Chinese students employ memorisation as an initial process in moving forward understanding rather than rote learning (Kember 2000, Tavakol andDennick 2010). Increasingly studies have found that Chinese students show little difference from their Western counterparts by being active learners and preferring meaning-based learning strategies and more interactive relationships with their teachers.…”
Section: Western Misconceptions Of Chinese Learnersmentioning
confidence: 99%
“…However, recent literature has challenged the view about the learning approaches and study practices of Asian students (Biggs 1996, Chalmers and Volet 1997, Chan 2001, Chan 1999, Kember 2000, Tan 2011, Tavakol and Dennick 2010. Instead, it is suggested that Chinese international students rote learn whilst using deep and achieving approaches concurrently (Tan 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Lee in Ryan and Louie (2007) have assorted aspects of Confucian beliefs for explanations of Asian students' certain attributes (e.g., positive attitude towards education) that have potential to lead to highly questionable over-generalizations. Another consequences of this 'surplus' perception lies within many researchers' assumptions that Asian values are "discrete, homogenous and unchanging" (Ryan & Louie, 2007, p. 405); these researchers for instance include: Tweed and Lehman (2002);Phuong-Mai (2005); Tavakol andDennick (2010) andFlynn (1992). However, operating within the 'surplus' theory is equally unhelpful as many scholars had little experience in Asia and "do not adequately take into account the dynamics of cultural adaptability (particularly in China)" (Drake, 2011, p. 225).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that in the typical classroom environment in Brunei, students rely on their teachers to acquire knowledge instead of independently searching or constructing knowledge. Such learning behaviors are consistent with traditional teaching methods that are associated with rote learning, which is an approach to learning that has historically benefited Asian cultures (e.g., Tavakol & Dennick, 2010), such as Brunei.…”
Section: Implications For Practicesupporting
confidence: 72%